Controlled dual release of dihydrotestosterone and flutamide from polycaprolactone electrospun scaffolds accelerate burn wound healing. Issue 5 (8th April 2022) - Shi, Huaikai; Tsai, Kevin H.‐Y.; Ma, Duncan; Wang, Xiaosuo; Desai, Reena; Parungao, Roxanne J.; Hunt, Nicholas J.; Cheng, Yuen Yee; Zhang, Hao; Xu, Ye; Simanainen, Ulla; Tan, Qian; et al.
Abstract: Wound healing is a complex process involving multiple independent and overlapping sequential physiological mechanisms. In addition to cutaneous injury, a severe burn stimulates physiological derangements that induce a systemic hypermetabolic response resulting in impaired wound healing. Topical application of the anti‐androgen drug, flutamide accelerates cutaneous wound healing, whereas paradoxically systemic dihydrotestosterone (DHT) improves burn wound healing. We developed and characterized a PCL scaffold that is capable of controlled release of androgen (DHT) and anti‐androgen (F) individually or together. This study aims to investigate whether local modification of androgen actions has an impact on burn injury wound healing. In a full‐thickness burn wound healing, mouse model, DHT/F‐scaffold showed a significantly faster wound healing compared with F‐scaffold or DHT‐scaffold. Histology analysis confirmed that DHT/F‐scaffold exhibited higher re‐epithelization, cell proliferation, angiogenesis, and collagen deposition. Dual release of DHT and F from PCL scaffolds promoted cell proliferation of human keratinocytes and alters the keratinocyte cell cycle. Lastly, no adverse effects on androgen‐dependent organs, spleen and liver were observed. In conclusion, we demonstrated DHT plus F load PCL scaffolds accelerated burn wound healing when loading alone did not. These findings point to a complex role of androgens in burn wound healing and open novel therapeutic avenues for treating severe burn patients.